Commemoration of Durruti. F.l.t.r.: Mas, Garcia Oliver, Domenech, ?, Puig Elias. Copied from CNT collection
Commemoration of Durruti. F.l.t.r.: Mas, Garcia Oliver, Domenech, ?, Puig Elias. Copied from CNT collection.